Inflammatory markers in lean Polycystic Ovary Syndrome subjects are not associated with the spectrum of dyslipidemia - Elisia Atnil; Andon Hestiantoro; Oki Riayati; Ririn Rahmala Febri; Naylah Muna (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Polycystic ovarian syndrome (PCOS) might be a condition of chronic low degree inflammation and dyslipidemia.2. Association between inflammation markers and dyslipidemia in PCOS patients was investigated.3. Dyslipidemia and chronic low degree inflammation were present in lean PCOS patients, but inflammation markers related insignificantly with dyslipidemia.   ABSTRACT Objectives: This study aimed to address the detailed lipid profile in lean woman with PCOS and investigate the relationship between chronic low grade inflammation (using NLR, PLR, and monocyte/HDL ratio) and dyslipidemia (defined as total cholesterol level > 190 mg/dL). Materials and Methods: This study was a cross-sectional study conducted from June – December 2020 at the Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Indonesia, Jakarta, Indonesia, involving 45 women aged 18 – 35 years old, diagnosed as having PCOS with normal BMI (18.5 – 22.9 kg/m2). To compare quantitative variables, data analysis was carried out using the t-test or Mann-Whitney U test as appropriate; whereas, to compare categorical variables, the Chi-square test was used. Results: We found that although the median BMI was within normal limits at 21.48 kg/m2, the mean values of the lipid profiles were found to be either abnormal or borderline, indicating the high possibility of dyslipidemia. No statistically association between NLR, PLR and MHR with dyslipidemia. Conclusion: Dyslipidemia and chronic low-grade inflammation were found in lean PCOS subjects, but there was no significant association between inflammation markers (NLR, PLR and MHR) and dyslipidemia. Further studies should investigate other factors that cause the inflammation.